Spatiotemporal patterns and potential sources of polychlorinated biphenyl (PCB) contamination in Scots pine (Pinus sylvestris) needles from Europe - Holt, Eva; Kočan, Anton; Klánová, Jana; Assefa, Anteneh; Wiberg, Karin (Environmental science and pollution research international, 2016)
Using pine needles as a bio-sampler of atmospheric contamination is a relatively cheap and easy method, particularly for remote sites. Therefore, pine needles have been used to monitor a range of semi-volatile contaminants in the air. In the present study, pine needles were used to monitor polychlorinated biphenyls (PCBs) in the air at sites with different land use types in Sweden (SW), Czech Republic (CZ), and Slovakia (SK). Spatiotemporal patterns in levels and congener profiles were investigated. Multivariate analysis was used to aid source identification. A comparison was also made between the profile of indicator PCBs (ind-PCBs-PCBs 28, 52, 101, 138, 153, and 180) in pine needles and those in active and passive air samplers. Concentrations in pine needles were 220-5100 ng kg(-1) (∑18PCBs - ind-PCBs and dioxin-like PCBs (dl-PCBs)) and 0.045-1.7 ng toxic equivalent (TEQ) kg(-1) (dry weight (dw)). Thermal sources (e.g., waste incineration) were identified as important sources of PCBs in pine needles. Comparison of profiles in pine needles to active and passive air samplers showed a lesser contribution of lower molecular weight PCBs 28 and 52, as well as a greater contribution of higher molecular weight PCBs (e.g., 180) in pine needles. The dissimilarities in congener profiles were attributed to faster degradation of lower chlorinated congeners from the leaf surface or metabolism by the plant.
Keywords: monitorování životního prostředí; Incineration; Spatial and temporal distribution; dioxiny; Europe; polychlorované bifenyly; Evropa; Plant Leaves; borovice lesní; Environmental Monitoring; Atmospheric pollution; Polychlorinated Dibenzodioxins; Bio-sampler; Polychlorinated Biphenyls; Active and passive samplers; Sources; Pinus sylvestris; Pine needle; Polychlorinated biphenyls; Dioxins; polychlorované dibenzodioxiny; listy rostlin; spalování odpadů